Association of renal ultrasonographic findings with elevated serum symmetric dimethylarginine in asymptomatic cats - Dea Gerez, Rafaelle Cristine; Fabiana Rodrigues de Freitas; Rosangela Locatelli Dittrich; Camila Marinelli Martins; Tilde Rodrigues Froes (Archives of Veterinary Science, 2025)
This study aimed to compare renal ultrasonographic findings with serum symmetric dimethylarginine (sSDMA) in asymptomatic cats. A prospective blinded study evaluated qualitative and quantitative ultrasound parameters in 101 cats without clinical signs of chronic kidney disease (CKD). Cats were grouped based on sSDMA levels: normal (≤14 µg/dL) or elevated (>14 µg/dL). Ultrasonographic abnormalities were scored (1–10) for statistical comparison. Of the 101 cats, 86 (85.15%) had normal sSDMA, while 15 (14.85%) exhibited elevated levels. Cats with increased sSDMA were more likely to show reduced corticomedullary differentiation (p=0.029), pelvic dilation (p=0.036), and ureteral calculi (p=0.04). A positive correlation was found between sSDMA and corticomedullary loss, whereas renal length showed a negative correlation with sSDMA. The overall correlation between sSDMA and ultrasonographic score was weak (r = 0.190, p = 0.057). Ultrasonographic variability was greater in cats with elevated sSDMA. In conclusion, asymptomatic cats with reduced corticomedullary differentiation, pelvic dilation, or smaller kidneys on ultrasound are more likely to have elevated sSDMA, suggesting early renal changes. These findings highlight the potential role of ultrasonography alongside sSDMA in detecting subclinical kidney disease in cats.